Food cue-induced craving in individuals with bulimia nervosa and binge-eating disorder - Meule, Adrian (PLoS One, 2018)
Individuals with bulimia nervosa (BN) or binge-eating disorder (BED) experience more frequent and intense food cravings than individuals without binge eating. However, it is currently unclear whether they also show larger food cue-induced increases in craving (i.e., food cue reactivity) than those without binge eating, as suggested by conditioning theories of binge eating. A group of individuals with BN or BED (binge-eating group, n = 27) and a group of individuals with low trait food craving scores and without binge eating (control group, n = 19) reported their current food craving before and after a food cue exposure. Although food craving intensity significantly increased in both groups, this increase was significantly stronger in the binge-eating group than in the control group. This result is in line with conditioning models of binge eating that propose that food cues are conditioned stimuli that elicit a conditioned response (e.g., food craving) and that this association is stronger in individuals with binge eating. As food craving increased in individuals with low trait food craving scores as well—although to a lesser extent—previous null results might be explained by methodological considerations such as not screening control participants for trait food craving.